Thyroid Gland Carcinosarcoma with Lung Metastasis in a Bitch - Santos Muniz Filho, Luis Carlos; Vieira da Silva, Guilherme Ramon; Moraes Milfont , Rayssa Taynara; de Melo Medeiros , Tainá Gabrielle; Brilhante Bezerra, José Artur; Dantas Filgueira, Kilder (Acta Scientiae Veterinariae, 2024)
Background: Thyroid gland neoplasia represents the most frequent endocrine tumor in dogs, corresponding from 10 to 15% of all head and neck tumors in this species. Thyroid carcinomas, followed by thyroid adenomas, are the histological types more frequently described. Another neoplasia that can affect the thyroid gland is the carcinosarcoma, which is a rare, aggressive, locally invasive tumor, with a high rate of metastasis, especially to the lungs. Thus, the present study aimed to report an uncommon case of thyroid gland carcinosarcoma with lung metastasis in a bitch. Case: A 9-year-old mixed breed bitch was admitted to the Veterinary Hospital of the Universidade Federal Rural do Semi-Árido (UFERSA) with a history of dyspnea, decreased appetite, and weight loss. On physical examination, the animal presented a poor body condition score. A mass was observed in the ventral cervical region, with a hard consistency. Moreover, the animal presented stridor and snoring on respiratory auscultation. Complementary exams were performed, including complete blood cell count, serum biochemistry, cervical ultrasonography, and thoracic radiography. The only abnormality observed on the biochemical profile was hypercalcemia (18.2 mg/dL). Cervical ultrasonography showed a neoformation with a great dimension, irregular contours, and heterogeneous echotexture, affecting the right and left thyroid lobes. The thoracic radiography demonstrated a diffuse nodular pattern, suggesting lung neoplasia. Due to the severity of clinical and imaging findings and the poor prognosis associated, a decision to euthanize the animal was made. A necroscopic examination was performed, which revealed a cervical bilobed neoformation adjacent to the tracheal rings. Both lungs were diffusely affected by nodules, with a hard consistency and irregular surface. Fragments of the neoformation adjacent to the trachea, as well as lung tissue samples were collected, fixed in formaldehyde, and sent for histopathological analysis. Microscopic evaluation of the tissue adjacent to the trachea revealed the presence of a carcinosarcoma in the thyroid gland, and analysis of lung tissue was similar to the findings observed in the thyroid. Thus, a diagnosis of primary carcinosarcoma in the thyroid gland with lung metastasis was defined. Discussion: In dogs, the etiology of thyroid neoplasia is still unknown, but hypothyroidism and ionizing radiation are reported as risk factors. Thyroid gland neoplasia represents 10 to 15% of all head and neck neoformations in dogs, being an important differential diagnosis for tumors in these regions. According to the literature, carcinosarcomas are rare and extremely invasive neoformations, and the treatment options and outcome depend on the size and invasiveness of the tumor. The prognosis in most cases is reserved or unfavorable, being better in the cases of early diagnosis. In the reported case, due to the late diagnosis, the animal was in an advanced stage of disease, with lung metastasis identified in the thoracic radiography, which limited the treatment options. During the necropsy, the thyroid neoformation was presenting adhesions to some structures, compromising part of the trachea and causing inspiratory dyspnea. The histopathological analysis confirmed an advanced, aggressive, and invasive case of carcinosarcoma in the thyroid gland with lung metastasis. Thyroid carcinosarcoma can be a challenging diagnosis in canine medicine and the late diagnosis often leads to a poor prognosis. Keywords: canine, endocrine neoplasia, thyroid neoplasia, oncology, vascular metastasis, Canis familiaris. Título: Carcinossarcoma de glândula tireoide com metástase pulmonar em uma cadela Descritores: canino, neoplasia endócrina, neoplasia de tireoide, oncologia, metástase vascular, Canis familiaris.